Epidemiological Profile of Meningitis in the State of Para, Amazonia between the Years 2018-2022 - , Thiago Augusto Ferreira Dos Anjos, Ana Paula Ferreira David, Aline Moraes Monteiro, Daniele Nunes Da Silva Ferreira, Larissa Mota Da Costa, Joana Wanderley Corrêa, Misma Suely Gonçalves Araújo De Lima, Josenilda Silva Moraes, Sebastião Kauã De Sousa Bispo, Sarah Caroline Gonçalves Furtado, Marcela Raíssa Asevedo Dergan (Archives of Current Research International, 2023)
Objective: Analyze the epidemiological profile of meningitis in the state of Pará, Amazon, from 2018 to 2022. Methodology: This is an ecological, retrospective, and descriptive-exploratory study, using data from the Information System for Notifiable Diseases (SINAN), made available on the website of the Department of Information of the Brazilian Unified Health System (DATASUS). Results: In the state of Pará, from 2018 to 2022, 1,680 cases were confirmed. The absolute number of cases per year was 508 (30%) in 2018. Males were the most affected with 966 cases (57.5%), and the age group of 20-39 years had the highest number of cases with 584. Regarding race, parda (mixed race) remains in first place with 1,472 cases. In terms of disease progression, the number of cases with a discharge is leading with 1,309, followed by the etiology, Viral Meningitis (MV), and Bacterial Meningitis (MB), which have the highest number of cases with a discharge. Conclusion: It can be inferred that the study in the state of Pará is essential for data collection and information regarding the disease, subsequently highlighting the main profiles and characteristics of the disease. Furthermore, the research proves to be important as the highest number of disease notifications occurred in the years 2018, 2019, and 2022.